Cubic interpolation profile Navier-Stokes numerical scheme for particle flow behaviour in triangular lid driven cavity - M. S., Idris; C. S. N., Azwadi; N. M. M., Ammar (AIP Publishing LLC., 2011)
Particle flow path in triangular lid driven cavity flow was simulated using the Cubic Interpolation Profile Method. Navier Stokes Equation was solved via Vorticity-Stream function approach for the case of triangular lid-driven cavity. Two models of triangular cavity were developed and the transient particle flow path in the cavity flow was monitored. Reynolds numbers of 800, 1000, 1200, 1500 and 2000 were simulated in the present study. We found that the particle trajectories were significantly affected by the transient behavior of the vortices in the cavity.